Association between interpersonal relational factors in couples with tubal infertility and delayed decision-making on definitive treatment: a case control study (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2016)
Background: Infertility affects about 10% of couples and is often characterized by delay in initializing seeking of  treatment, which culminates in delay in appropriate decision-making on definitive management. This creates a  need for understanding the determinants of delay in order to strategize on corrective intervention. Objective: To determine the association between interpersonal relational factors among couples with tubal  infertility and delayed decision-making on definitive treatment. Method: This was an unmatched case-control study at Kenyatta National Hospital Infertility Clinic amongst women  with tubal infertility in who decisions on definitive treatment had been made. Cases were patients with delayed  decision-making (≥4 years), whereas controls were patients without delayed decision-making (35 years (OR 15.93, OR 95% CI 5.36-47.38, p